Foreign direct investment, workers’ remittances and private saving in Pakistan: an ARDL bound testing approach - Raza, Syed Ali (Journal of Business Economics and Management, 2015)
The objective of this study is to investigate the impact of foreign direct investment (FDI) and workers’ remittances on private savings of Pakistan. This study employs ARDL bound testing co-integration approach, rolling window analysis, Granger causality test, Toda and Yamamoto Modified Wald causality test and variance decomposition test. Results indicate the significant positive impact of FDI and workers’ remittances on private savings in the long and short run. Causality analyses confirm the bidirectional causal relationship of FDI and workers’ remittances with private savings. It is recommended that policy makers should form friendly policies to attract more FDI and workers’ remittances in the country which leads to increase private savings in Pakistan. This leads to increase more fund for financial intermediaries to increase domestic investment opportunities in the country. This paper makes a unique contribution to the literature with reference to Pakistan, being a pioneering attempt to investigate the impact of FDI and workers’ remittances on private savings of Pakistan by using the long annual time series data and applying more rigorous econometric techniques.